DEKONSTRUKSI KEADILAN DALAM POLIGAMI: : Membaca Ulang Perlindungan Istri Pertama dalam dialektika Hukum Perkawinan di Indonesia. - Syaf, Moh. Najib (LPPM UNHASY, 2025)
Ostensibly characterized as among the most progressive in the Muslim world, Indonesia’s polygamy regulations—codified under Law No. 1/1974 and the Compilation of Islamic Law (KHI)—persistently fail to mitigate the socio-legal precarity of first wives due to systemic procedural circumvention. This research interrogates the functional failures in safeguarding the rights of first wives through the analytical lens of Maqasid al-Shari’ah (teleological legal reasoning). Utilizing a normative-juridical approach, the study delineates a state of